2009
DOI: 10.1002/mawe.200900434
|View full text |Cite
|
Sign up to set email alerts
|

Influence of grain size on mechanical and corrosion properties of magnesium alloy for medical implants

Abstract: The microstructure, mechanical property and corrosion behavior of magnesium alloy WE43 (MgYNdZr alloy) in the environment simulating biological fluid were investigated. Samples of ultrafine-grained magnesium alloy with high mechanical properties were obtained by methods of severe plastic deformation. Programmed plastic deformation was realized by two methods: extrusion alternating with upsetting at gradually lowering the temperature and equal-channel angular pressing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 8 publications
3
29
0
2
Order By: Relevance
“…However, some researchers reported that Mg alloys with finer grains show higher corrosion rate (Kutniy et al, 2009;Song et al, 2011). Song et al (2011) reported that the corrosion resistance of the ultra-fine grained AZ91D alloy is lower than that of the as-cast AZ91D alloy.…”
Section: Grain Refinementmentioning
confidence: 99%
“…However, some researchers reported that Mg alloys with finer grains show higher corrosion rate (Kutniy et al, 2009;Song et al, 2011). Song et al (2011) reported that the corrosion resistance of the ultra-fine grained AZ91D alloy is lower than that of the as-cast AZ91D alloy.…”
Section: Grain Refinementmentioning
confidence: 99%
“…8 As highlighted by disparate results from a number of recent studies related of Mg and Mg alloys in various environments, grain size can have a varied effect on corrosion rate. [9][10][11][12][13][14][15][16] A survey of these works provides little consensus as to an all-encompassing effect. However, the most relevant conclusions to this study indicate that the pure Mg (grain-refined through equal channel angular pressing [ECAP]) can alternately decrease 10,13 or increase 15 corrosion rate depending on the sodium chloride (NaCl) concentration-0.1 mol dm -3 NaCl and 3.5% NaCl (~0.6 mol dm -3 ), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…From these observations, it is clear that BG particles in the ZK30‐10%BG composites play an important role in improving the corrosion resistance of the matrix alloy. For the ZK30 alloy, a layer of Mg(OH) 2 forms on sample surface at the initial stage of immersion and it is however, still susceptible to attack from acidic ions in the immersion medium such as Cl− ions 32. The following reaction takes place to undermine the integrity of the Mg(OH) 2 layer: Cl− ions are able to penetrate into the inner part of the material through, for example, grain boundaries.…”
Section: Resultsmentioning
confidence: 99%